Sevoflurane protects cardiomyocytes against hypoxia/reperfusion injury via LINC01133/miR-30a-5p axis. Issue 12 (23rd December 2020) - Yu, Zhenyi; Ren, Qiusheng; Yu, Shenghui; Gao, Xiang
Abstract: Previous studies failed to elucidate the detailed mechanisms of anesthetic preconditioning as a protective approach against ischemic/reperfusion (I/R) injury in cells. The present study mainly centered on discovering the mechanisms of Sevoflurane (Sev) in preventing cardiomyocytes against I/R injury. Human cardiomyocyte AC16 cell line was used to simulate I/R injury based on a hypoxia/reperfusion (H/R) model. After Sev treatment, cell viability and apoptosis were detected by MTT assay and flow cytometry, respectively. Lactate dehydrogenase (LDH) content was measured using an LDH Detection Kit. Relative mRNA and protein expressions of LINC01133, miR-30a-5p and apoptosis-related proteins were detected using quantitative real-time polymerase chain reaction (qRT-PCR) and Western blot as needed. Target gene of miR-30a-5p and their potential binding sites were predicted using Starbase and confirmed by dual-luciferase reporter assay. Cell behaviors were assessed again after miR-30a-5p and LINC01133 transfection. Sev could improve cell viability, reduce LDH leakage, and down-regulate the expressions of apoptosis-related proteins (Bax, cleaved caspase-3 and cleaved caspase-9) and LINC01133 as well as up-regulate miR-30a-5p and Bcl-2 expressions in H/R cells. MiR-30a-5p was the target of LINC01133, and up-regulating miR-30a-5p enhanced the effects of Sev in H/R cells, with a suppression on H/R-induced activation of the p53 signaling pathway. However, up-regulating LINC01133 reversed the enhancing effects of miR-30a-5p on Sev pretreatment in H/R cells. Sev could protect cardiomyocytes against H/R injury through the miR-30a-5p/LINC01133 axis, which may provide a possible therapeutic method for curing cardiovascular I/R injury.